2015
DOI: 10.1089/cyber.2014.0362
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Adolescents' Involvement in Cyberbullying: What Divides the 20% from the 80%?

Abstract: Despite some variations among cyberbullying studies, about 20% of the youth population surveyed appears to be involved in cyberbullying. Coincidentally, the current study found that exactly 20% of the students surveyed were involved in cyberbullying as bullies (7.8%), victims (7.5%), and bully/victims (4.7%). What divides those 20% from the 80% of noninvolved students? This study aimed to produce a parsimonious and accurate model that can predict the occurrence of involvement in cyberbullying among youth. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…Furthermore, there was a significant degree of variability in the nature of the questions posed by the study authors. For example, some researchers focused their questions on negative comments to postings (21), some focused on the media that was used (22), others focused on the number of cyberbullying incidents during a particular time period (23), and still others focused on the emotional impact of the interaction (24,25). This suggests the need for a standardized set of questions that focuses on content and disregards platform.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there was a significant degree of variability in the nature of the questions posed by the study authors. For example, some researchers focused their questions on negative comments to postings (21), some focused on the media that was used (22), others focused on the number of cyberbullying incidents during a particular time period (23), and still others focused on the emotional impact of the interaction (24,25). This suggests the need for a standardized set of questions that focuses on content and disregards platform.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that 20% of the youth population surveyed was involved in cyberbullying either as a victim, a bully, or both. The study further showed that younger students who spent more time playing games on weekdays while being more confident in cyberspace and active in using mobile phones are more likely to be involved in cyberbullying than other students ( Shin and Ahn, 2015 ). Another study revealed that Facebook and text messaging were the most frequent mediums for cyberbullying and that sexual-minority students and students who texted at least 50 times per day were more likely to report cyberbullying victimization ( Rice et al., 2015 ).…”
Section: Related Workmentioning
confidence: 95%
“…Loneliness is also associated with increased use of the internet and the problematic use of smartphones [28,29]. Adolescents who are victims of bullying try to find virtual friends in order to obtain emotional support to alleviate negative moods associated with loneliness, which can likely lead to greater risks of cyber abuse [30].…”
Section: Cybervictimizationmentioning
confidence: 99%